The Gut Microbiome Alterations in Pediatric Patients with Functional Abdominal Pain Disorders - Bassam Abomoelak (MDPI AG, 2021)
In this prospective longitudinal study, we enrolled 54 healthy pediatric controls and 28 functional abdominal pain disorders (FAPDs) pediatric patients (mean age was 11 ± 2.58 years old). Fecal samples and symptom questionnaires were obtained from all participants over the course of the year. Clinical data assessment showed that FAPDs patients were more symptomatic than the control group. Microbiome analysis revealed that Phylum Bacteroidetes was higher in FAPDs compared to the control group (p < 0.05), while phylum Firmicutes was lower in FAPDs (p < 0.05). In addition, Verrucomicrobiota was higher in the control group than the FAPDs (p < 0.05). At the genus level the relative abundance of 72 bacterial taxa showed statistically significant differences between the two groups and at the school term levels. In the control group, Shannon diversity, Observed_species, and Simpson were higher than the FAPDs (p < 0.05), and beta diversity showed differences between the two groups (PERMANOVA = 2.38; p = 0.002) as well. Using linear discriminant analysis effect size (LEfSe), Enterobacteriaceae family and Megaspherae showed increased abundances in vacation term (LDA score > 2.0, LEfSe, p < 0.05). In the FAPDs group, the severity of symptoms (T-scores) correlated with 11 different taxa bacterial relative abundances using Pearson′s correlation and linear regression analyses. Our data showed that gut microbiome is altered in FAPDs compared to the control. Differences in other metrics such as alpha- and beta diversity were also reported between the two groups. Correlation of the severity of the disease (T-scores) correlated with gut microbiome. Finally, our findings support the use of Faecalibacterium/Bacteroides ratio as a potential diagnostic biomarker for FAPDs.